WOMEN’S LANGUAGE IN JENNY HAN’S SERIES “THE SUMMER I TURNED PRETTY” - Anggraeni, Yuni; Iskandar, Iskandar; Bakri, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research discusses the language of women contained in the series 'The Summer I Turned Pretty'. This research aims to analyze the female language contained in the series 'The Summer I Turned Pretty' by using Lakoff's theory (1973 & 1975) to analyze ten features of women’s language. The research method used in this study is descriptive qualitative method. The researcher analyzed the women’s language in the series 'The Summer I Turned Pretty' which amounted to 7 episodes and lasted about 45 minutes each. The result of this study shows that 10 features of female language were found in the series. The features of women’s language including lexical hedges or fillers, tag questions, rising intonation on declaratives, empty adjectives, precise color terms, intensifiers, hypercorrect grammar, ‘superpolite’ forms, avoidance of strong swear words, and emphatic stress. The reason women use the features of the female language is because to cover themselves from self-confidence or make them feel confident when using these features. From the 10 data observed, the researcher concludes that some features have similar purposes but different uses.